Geoinformation for Informed Decisions - Abdul Rahman, Alias; Boguslawski, Pawel; Anton, François; Said, Mohamad Nor; Omar, Kamaludin Mohd (Lecture Notes in Geoinformation and Cartography, 2014)
This book presents the latest research developments in geoinformation science, which includes all the sub-disciplines of the field, such as: geomatic engineering, GIS, remote sensing, digital photogrammetry, digital cartography, etc.